MENINGKATKAN PEMAHAMAN KONSEP SISWA MELALUI TEAMS GAMES TOURNAMENT (TGT): META ANALISIS - Fitriyane Laila Apriliani Rahmat; Suwatno Suwatno; Rasto Rasto (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
This paper aims to analyze specifically about effort to improve students' conceptual understanding through Teams Game Tournament (TGT) learning method. This analysis is based on a number of relevant articles of 30 articles, both partially and correlatively discussed. The results of the analysis of the whole article shows that cooperative learning method of TGT can improve students' concept understanding. This paper can provide implications for teacher, to make the TGT method as an alternative choice in improving students' concept.